Pengembangan Manajemen Homestay di Ubud Dengan Membangun Inovasi Digital Melalui Sistem Informasi - Ni Made Intan Kusumasari; Putu Ayu Trisna Febrianty; Dhea Fitrisia; Christina Ayu Maha Dewi (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
This community service project highlights the role and impact of homestay in Ubud’s tourism, with a specific focus on Gusti Homestay Ubud. The primary goal of this initiative is to develop an information system that strengthens the homestay’s presence and enhances the quality of services provided to guests. To achieve this, various research methods have been employed, including a SWOT analysis, online platform development, and the implementation of digital marketing strategies. The outcomes of this project include the launch of Google Business, an official website, and social media accounts designed to increase the visibility and accessibility of the homestay. These efforts are expected to attract more tourists, boost the income of the homestay owner, and offer guests a better and more satisfying stay experience. Consequently, this project not only strengthens the position of Gusti Homestay within the local tourism industry but also contributes to the economic growth of Ubud and enhances the appeal of the destination as an attractive tourist spot